Analisis Kebutuhan Fasilitas Pedestrian di Kawasan Stasiun - Adilah, Anisah; Buchari, Erika; Agustien, Melawaty (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2024)
The Ampera LRT Station is located in the center of Palembang City and on the banks of the Musi River. This area is a center of community activity, with the presence of hospitals, offices, restaurants, hotels, and shopping centers. The existence of the Palembang LRT is intended to overcome congestion and accommodate the mobility needs of the community in Palembang, especially in the Ampera area. However, there are several issues related to pedestrian facilities in the Ampera LRT Station area, such as the misuse of sidewalk functions, the presence of many side barriers in the form of street vendors and on-street parking, as well as the lack of safe and comfortable crossing facilities for pedestrians, especially for people with disabilities. This study analyzes the pedestrian facility needs in the Ampera LRT Station area of Palembang. The method used in this study is the calculation of the level of service (LOS) based on the Indonesian Highway Capacity Manual (MKJI) 1997 and the empirical formula calculation of pedestrian conflicts based on the pedestrian flow and vehicle traffic flow (PV2) using quantitative data. The research results show that it is necessary to repair and add pedestrian facilities under the concept of walkability, such as providing sidewalks that can be used according to their function, providing crossing facilities such as pelicans with waiting platforms on Merdeka Street, Sudirman Street, and Tengkuruk Permai Street, while on Masjid Lama Street and Palembang Darussalam Street, zebra crossings or pedestrian platforms are needed. The results of this study are expected to be input for the Palembang City Government to improve the quality of pedestrian facilities in the Ampera LRT Station area so that it can support the station's function as a center of community activity and movement in the area.